Human Gesture Evaluation with Visual Detection and Haptic Feedback - Barbosa, Camila; Souza, Luiz Felipe; Lima, Erickinson de; Silva, Bruno; Santana Jr., Orivaldo; Alberto, Gabriel (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2018: Proceedings of the 24th Brazilian Symposium on Multimedia and the Web, 2018)
Learning a gesture pertains to learning a expression of motion by a human, involving the hands, arms, face, head, and/or body. In this work, we propose to employ haptic feedback as an additional tool in the gesture following/evaluation loop. Accordingly, the user wears a haptic wearable device in the form of a bracelet which vibrates according to the trajectory error. Our research hypothesis is then to investigate whether such haptic device aids the user in correcting his movement in relation to the prerecorded trajectory.